Predicting Nutrient Incontinence in the Anthropocene at Watershed Scales - Frei, Rebecca J.; Abbott, Benjamin W.; Dupas, Remi; Gu, Sen; Gruau, Gerard; Thomas, Zahra; Kolbe, Tamara; Aquilina, Luc; Labasque, Thierry; Laverman, Anniet; Fovet, Ophelie; Moatar, Florentina; et al. (Frontiers in Environmental Science, 2020)
Quantifying nutrient attenuation at watershed scales requires long-term water chemistry data, water discharge, and detailed nutrient input chronicles. Consequently, nutrient attenuation estimates are largely limited to long-term research areas or modeling studies, constraining understanding of the ecological characteristics controlling nutrient attenuation and complicating efforts to protect or restore water quality in developed and developing regions. Here, we combined long-term data and a broad suite of biogeochemical parameters from 49 watersheds in northwestern France to test how well instantaneous measurements can predict nitrogen (N) and phosphorus (P) attenuation at watershed scales. We evaluated 13 biogeochemical and 12 hydrological proxies of hydrological flowpaths, residence time, and biogeochemical transformation. Across the 49 watersheds, nutrient attenuation ranged from 88 to -2% for N and 99 to 96% for P. The strongest biogeochemical proxies of N attenuation were NO3- isotopes, rare earth elements, radon, and turbidity, together explaining 75% of observed variation. For P attenuation, rare earth elements, NO3- isotopes, molecular weight of dissolved organic matter, and radon were the strongest proxies, but only explained 27% of observed variation. However, a single hydrological parameter—annual runoff—explained 91% of N attenuation and the relative abundance of schist bedrock explained 56% of P attenuation. We discuss how runoff both controls and reflects watershed hydrology, biogeochemistry, and nutrient attenuation. For example, runoff was correlated with long-term decreases in nutrient concentration, demonstrating how leakier watersheds recover more quickly from nutrient saturation. Given the immense fertilization capacity of modern society, we propose that eutrophication can only be solved by reducing nutrient inputs, though hydrochemical proxies can provide valuable information on where to carry out essential food production activities.